Genetic variability in fenugreek (Trigonella foenum-graecum L.) grown under mid-hills of Himachal Pradesh - Korla, Rakesh Verma, B N (Journal of Spices and Aromatic Crops, 2003)
Thirty nine accessions of fenugreek (Trigonella foenum-graecum L.) were collected from different parts of the country and evaluated under mid-hill conditions of Himachal Pradesh. The coefficient of variation was high for economic yield and biological yield in these accessions. Heritability in broad sense was high for plant height, seed vigour and pods plant-1 while moderate for 1000-seed weight, branches plant-1, total seedling length and germination percentage. Economic yield, biological yield and pod length exhibited low heritability. Genetic advance as percentage of mean was comparatively high for biological yield, economic yield and pods plant-1.